Letramentos digitais e ensino: uma análise a partir da olimpíada nacional em história do Brasil - Negócio, Polianny Ágne de Freitas (2020)
The emergence of digital technologies, in the 20th century, revolutionized and transformed the multiple sectors of society, thus also transforming social practices, experiences in the urban space and the way to consume information. In this sense, we reflect on the impacts of these transformations on the categorization of new literacies and aim to investigate the digital literacies included in the resolution of issues of the National Olympiad in the History of Brazil -ONHB, exploring the skills required in this process. In order to reach the proposed objective, a field research was carried out, of the pilot case study type, with nine students from the Federal Institute of Education, Science and Technology of Rio Grande do Norte – IFRN. The reason for choosing the institute is because it is a public school with active participation of students and faculty at ONHB and the selection criteria for students were based on the experience they already have with the process of resolving the issues, as it is necessary know how the methodology works before solving them and it was not our objective to carry out any intervention. In a competitive environment, the experience takes place via the internet, on an interactive platform and system, and the questions work on themes from the perspective of historical documents, images, maps, academic texts, unprecedented research and historiographical debates, bringing four alternatives. The methodological difference of the evaluation is that more than one alternative is correct, being attributed to these scores of zero, one, four or five. Data collection was carried out outside the competitive scope of the Olympics, considering that the questions are made available by the organizing committee in a database, which can be accessed and used free of charge by students and teachers on its own website and the procedures listed in the monitoring consisted of in: a) recording computer webs and students' voices during the resolution process using the loom tool and b) systematically observing the actions, which constituted the research corpus. The analysis was carried out in the light of the New Literacy Studies; also based on Knobel and Lankshear (2003;2006;2007;2013) to discuss the elements that constitute the new literacies, culminating in the so-called digital literacies. The concepts of literacy and literacy were based on Soares (1985;2003;2004) and Kleiman (1995) and the reading and writing relationships in print and in the digital environment were understood with the support of Coscarelli (2007;2003;2016) ;2017;2019) and Ribeiro (2008;2009;2020); Lemos (2004;2005) and Bianchatti (2001) helped us to draw a historical overview of the transformations of technologies and their social impacts. Based on the research, it was possible to verify that digital literacy is covered by the ONHB, not only because the Olympics are developed in an online environment, but also because students need to read and navigate, assuming a new mentality, through an investigative posture in the face of digital technologies, to locate and evaluate content, synthesize and integrate information and reflect collectively, collaboratively, interactively and decentralized in the construction of knowledge. The discussions held foster the debate on digital literacies and bring contributions to education by reflecting on the potential of digital technologies extended to a view that these technologies are not just a means of performing a certain action with a technological tool, but rather a a new attitude towards reality, assuming a new way of thinking and acting focused on the collectivity as a unit of production, competence and intelligence